3D modellling editor for mobile application using augmented reality technology - Nur Fahimah Abd. Razak, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik dan Multimedia)) - Universiti Teknologi Malaysia, 2017